Different Trajectories of Prolonged Grief in Bereaved Family Members After Terror - Kristensen, Pål; Dyregrov, Kari; Gjestad, Rolf (Frontiers in Psychiatry, 2020)
Introduction: The loss of a loved one in a terror incident is associated with elevated risk for mental health problems such as prolonged grief disorder (PGD) and posttraumatic stress disorder (PTSD), but the long- term trajectories of PGD after terror are not well understood. This study aims to explore the trajectories of PGD among parents and siblings (n=129) after the 2011 terror attack on Utøya Island, Norway. Methods: The 19-item Inventory of Complicated grief (ICG) was used to measure PGD at 18, 28, and 40 months post-loss. A latent class growth analysis approach (LGCA) was used to identify trajectories of grief and a multinomial regression analysis was conducted to examine predictors of class membership. Results: The LGCA analysis identified three grief trajectories; moderate/decreasing class (23%), high/slow decreasing class (64%), and a high/chronic class (13 %). Predictors of chronic grief was female gender, previous depressive symptoms, and intrusion and avoidance symptoms. Conclusion: The findings highlights the long-lasting and slow recovery of grief among the majority of close family members bereaved by a terror-incident. This underlines the importance of an early outreach strategy, and that mental health clinicians are skilled in assessment and treatment of both PGD and PTSD.